ENSO and QBO modulation of the relationship between Arctic sea ice loss and Eurasian winter climate. (1st December 2022) - Ma, Xuan; Wang, Lei; Smith, Doug; Hermanson, Leon; Eade, Rosie; Dunstone, Nick; Hardiman, Steven; Zhang, Jiankai
Abstract: The causality between Arctic sea ice decline and cold boreal winters has been widely debated recently and remains controversial. A major source of uncertainty in the sea ice-cold winter relationship originates from that the stratosphere polar vortex (SPV) is not only affected by Arctic sea ice anomaly but can also be modulated by El Niño-Southern Oscillation (ENSO) and quasi-biennial oscillation (QBO). Using reanalysis data and hindcasts from the decadal prediction system version 4, here we show that both cold and warm winters occur over Eurasia when the Barents–Kara Sea sea ice is abnormally low. Warm winters occur during the La Niña-easterly QBO-low sea ice (LANINA-EQBO-LICE) years and cold winters during the neutral ENSO-neutral QBO (NENSO-NQBO)-LICE and El Niño (ELNINO)-NQBO-LICE years. During the LANINA-EQBO-LICE years, weakened upward-propagating planetary waves from the troposphere to the stratosphere strengthen the Arctic SPV and then weaken the Aleutian low and Siberian high, creating conditions favorable for Eurasian warming. The atmospheric responses are opposite in the NENSO-NQBO-LICE and ELNINO-NQBO-LICE years. This implies that care should be taken in using Arctic sea ice alone as the precursor to predict boreal winter climate.